Can green bonds hedge against geopolitical risk? A cross-market connectedness analysis with portfolio implications - Xia, Yufei; Chen, Yujia; He, Lingyun; Shi, Zhengxu; Ji, Xintian; Cai, Rongjiang (Technological and Economic Development of Economy, 2025)
This study investigates whether green bonds (GBs) can hedge against geopolitical risk (GPR). This study extends the booming literature on GPR and GBs, develops a modified connectedness network model to measure the connectedness between GPR and GBs, confirms the hedging property of GBs against GPR, and becomes the first to discuss alternative hedging properties of GBs against GPR. We find evidence of market-, time-, and quantile-varying linkage between GPR and GB markets based on the time-varying Granger causality test and quantile extended joint spillover index model. We confirm via a regression model that only the GB markets in China and Japan can hedge against GPR. At the same time, GB in China remains a weak hedging and safety-haven asset simultaneously. The results remain robust for alternative proxy variables, data frequency, and model specification. Finally, the MVP approach provides superior performance while maintaining weak hedging and safety-haven properties against GPR. This study has considerable portfolio-related implications: (1) it offers an efficient hedge (i.e., GB) against GPR, (2) the heterogeneous performance of regional GB markets reminds investors to be cautious when selecting GBs assets, and (3) it encourages reasonable investment allocations on GBs to achieve a balance between profit and risk. First published online 24 September 2024